2011
DOI: 10.1258/jms.2011.011092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of media reporting of cervical cancer in a UK celebrity on a population-based cervical screening programme

Abstract: Objectives To determine the impact of media reporting of cervical cancer in a UK celebrity on cervical screening uptake, response time and colposcopy referral and attendance. Setting Population-based national cervical screening programme for women in Wales, UK. Methods A time series regression analysis of the Welsh national cervical screening and colposcopy databases was used to examine the number of smear tests carried out between 2000 and 2010, stratified by age group and deprivation indicators. Logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
(68 reference statements)
0
36
1
1
Order By: Relevance
“…21 Women from lower SEC groups and with fewer educational qualifications were more likely to say they had been influenced by Goody's story. This contrasts with data showing no association between area-level deprivation and attendance at cervical screening in Wales after her death; 9 however, it is possible that area-level deprivation measures are too crude to identify fine-grained socioeconomic patterning. Goody was from a lower socioeconomic background herself, and so these groups of women may have identified with her more strongly.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…21 Women from lower SEC groups and with fewer educational qualifications were more likely to say they had been influenced by Goody's story. This contrasts with data showing no association between area-level deprivation and attendance at cervical screening in Wales after her death; 9 however, it is possible that area-level deprivation measures are too crude to identify fine-grained socioeconomic patterning. Goody was from a lower socioeconomic background herself, and so these groups of women may have identified with her more strongly.…”
Section: Discussioncontrasting
confidence: 58%
“…Consistent with previous data from the national screening programme, women from younger age groups seemed to be most influenced by Goody's story. 5,9 Having had children at a younger age was also associated with being influenced by Goody's story. One explanation for these women being particularly influenced by the story is that Goody herself was young (27 when she died) and had two young children.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of celebrity cases on UK national newspaper coverage was observed in varying degrees across all of the cancer types studied, although some were of relatively low-profile cases compared with the well-studied example of television celebrity Jade Goody whose experience with cervical cancer increased screening among British women 30 31. In the USA, cases of bowel cancer associated with high-profile figures has also led to a corresponding increase in the use of early detection tests 32 33…”
Section: Discussionmentioning
confidence: 98%
“…Impact of media reporting of cervical cancer in a UK celebrity on a population-based cervical screening programme (29) 2011/ United Kingdom Ecological/ 33,000 Media reports about celebrities Showed a transitory increase in Pap smear exams rate…”
Section: Educational Intervention With Workhopsmentioning
confidence: 99%
“…A study carried out with women in Wales, United Kingdom, showed that media articles play an important role in increasing the uptake of Pap smear exams (29) . Likewise, a quasi-experimental study with women in Southeast Asia found an increase in knowledge and adherence to exams through a thematic soap opera and the use of educational flyers (30) .…”
Section: Media Outreach Workmentioning
confidence: 99%